Uma experiência com a essência da modelagem matemática na construção de maquete - Haliski, Antonio Marcos (2010)
Sought through this work entitled "experience with the essence of Mathematical Modelling in building model", to address content forming part of the school curriculum through the construction of the maquette of the College, with the active participation of the learners. That way, into context education but also making a closer relationship between scientific knowledge and the daily for the purpose of enabling the acquisition of knowledge in teaching-learning process. Thus, had employment of because it allowed the teacher/researcher provide the effective participation of pupils in the course of the project for which through collections materials such as pre and post testing, observations and analysis of the results obtained could make a critical analysis concerning the methodology adopted in the light of Piaget theory Construtivista. Thus, the audience were two classes of 1st series high school college Estadual Heráclito Fontoura Sobral Pinto in Colombo - PR, in which the class A worked the theory with practice correlated with the construction of the maquette (Mathematical Modelling). While with the class B, worked the same content, but only in theoretical form (traditional). The intention to use different methodologies with two classes was to make a critical analysis of the effectiveness and performance of learners when using the Mathematical Modelling within schools. In this context, realized both classes have a good return on the acquisition of mathematical knowledge. However, class A, presented a more satisfactory result, as has also been greater proximity between teacher-student and student-student, if compared with the class B. Noticed that when working the contents theoretically allies with the practice, the students had greater understanding and interaction with the object of study, as a consequence of better assimilation of mathematical content. In addition, the class A, showed greater creativity in the development of work, so, assuming interest them, using computational software built the maquette College in 3D. The finalization of the work happened with the presentation of students to the school community, demonstrating the specific material (maquette), but also the presentation model in 3D, along with the exposure of the Panel of photos depicting the development work. This way, is possible to say that employ Mathematical Modelling in practical schools is one of the features that the educator can resort in order to work with the contents of the discipline of mathematics into context, thereby students significant results in learning and opportunitying them to use their imaginations, breaking out, criticism and reflected within the context of social history.